2020
DOI: 10.3892/ol.2020.12038
|View full text |Cite
|
Sign up to set email alerts
|

High expression of eIF4A2 is associated with a poor prognosis in esophageal squamous cell carcinoma

Abstract: Eukaryotic initiation factor 4A-II (eIF4A2) is an ATP-dependent RNA helicase involved in mRNA translation. Abnormal expression of eIF4A2 has been reported as a prognostic factor in different types of cancer. However, little is known regarding the function of eIF4A2 in esophageal squamous cell carcinoma (ESCC). In the present study, 253 samples were collected from patients diagnosed with ESCC, and the expression of eIF4A2 was detected by immunohistochemical staining. The clinicopathological and prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In esophageal squamous cell carcinoma, eIF4A2 has been found to be more highly expressed in neoplastic tissues than in normal tissues, and patients with high expression levels of eIF4A2 tend to have a poorer prognosis (Lyu et al, 2020). Furthermore, the univariate and multivariate analyses have suggested that eIF4A2 is an independent prognostic factor in esophageal squamous cell carcinoma (Lyu et al, 2020).…”
Section: Expression Patterns Of Eif4a1 and Eif4a2 In Breast Cancermentioning
confidence: 99%
“…In esophageal squamous cell carcinoma, eIF4A2 has been found to be more highly expressed in neoplastic tissues than in normal tissues, and patients with high expression levels of eIF4A2 tend to have a poorer prognosis (Lyu et al, 2020). Furthermore, the univariate and multivariate analyses have suggested that eIF4A2 is an independent prognostic factor in esophageal squamous cell carcinoma (Lyu et al, 2020).…”
Section: Expression Patterns Of Eif4a1 and Eif4a2 In Breast Cancermentioning
confidence: 99%
“…Since the majority of studies support the involvement of p-eIF4E in cancer progression, future studies should investigate the effects of AA on the phosphorylation status of this protein. Recently, high levels of eIF4A2 were associated with poor prognosis in esophageal squamous cell carcinoma [64].…”
Section: Discussionmentioning
confidence: 99%
“…The two are largely redundant and will be interchangeably referred to as DDX2, although there is emerging evidence of different functions in vivo [306] , [307] . A specific role of DDX2B in esophageal squamous cell carcinoma was recently reported [308] . DDX2 upregulation drives translation reprogramming in pancreatic [309] , [310] , breast [311] , [312] and other cancers [302] , [313] , [314] , [315] .…”
Section: Introductionmentioning
confidence: 95%